Management of occlusion in a full edentulous with abnormal jaw relation: Penanganan oklusi pada edentulous totalis dengan hubungan rahang abnormal - Eri Hendra Jubhari; Andi Novi Patilasarani (Makassar Dental Journal PDGI Makassar, 2020)
The successful of complete denture treatment depends on functional factors: retention, stability and support. Mandibular prognathism due to under development of the maxilla or excessive development of the mandible. Harmonious denture occlusion leads to the level of patient satisfaction with the denture, ability and efficiency of masticatory function; the importance of arrangement artificial teeth with stable occlusion in maintaining the stability of denture. This article is aimed to discuss about management occlusion in totally edentulous patient with abnormal jaw relationship. The arrangement of anterior artificial teeth in mandibular protrusion are set edge to edge. In the case of the mandibular-ridge is wider than the maxillary if the difference in size of the jaw is minimal, it can be managed by arranged the maxillary posterior artificial teeth more buccal so that it will have a satisfactory occlusal relationship with the opposing mandibular posterior teeth. Non-anatomical teeth can be used to provide freedom in buccolingual placement and adequate occlusal contact. If the abnormality of mandibular is too wide, then the cross-arch arrangement posterior artificial teeth is advised.